Importance of Implementation of Digital Nomad Visa in Order to Reduce Immigration Violations - Uray Vini Octavia (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
As a tourist destination for Digital Nomads.During the pandemic in the last two years, immigration policies have restricted a number of foreigners, especially foreigners with visa-free visits, where this type of visa is the type of visa that is widely used by Digital Nomads to enter Bali. There are many violations related to Digital Nomad, one of which is Cristen Gray, who during this pandemic actually invited tourists to enter Bali amid the policy of restricting the entry of foreigners into Indonesian territory. On the other hand, the Balinese economy, which heavily relies on tourism, has experienced an economic decline. Therefore, look at the security conditions due to immigration violations and the condition of the need to revive the Balinese economy through tourism. The author is then interested in seeing the extent of the implementation of the Digital Nomad visa in order to reduce immigration violations. The purpose of this study is to determine the urgency of the Digital Nomad visa in reducing the number of violations of the misuse of immigration visit residence permits, as well as to determine the mechanism of the Digital Nomad visa in the Indonesian visa system. This research is normative-empirical legal research. The results of this study indicate that the urgency of regulation from Digital Nomad is the potential of Digital Nomad Foreigners and Digital Nomad culture that is currently developing in the world to improve the domestic economy through tourism in special tourist areas. For the opportunity to regulate the Digital Nomad visa, it depends on the arrangement of digital work patterns and the determination of administrative factors in the form of terms and conditions in terms of the large number of security deposits that can screen foreigners who have the potential to benefit the Indonesian people.